Strengthening Executive Function and Self-Regulation Through Teacher-Student Interaction in Preschool and Primary School Children: A Systematic Review - Sankalaite, Simona; Huizinga, Mariëtte; Dewandeleer, Jolien; Xu, Canmei; de Vries, Nicky; Hens, Emma; Baeyens, Dieter (Frontiers in Psychology, 2021)
Executive functions (EF) and self-regulation (SR) are fundamental for children’s learning, school functioning and academic achievement. EF/SR fail to develop to its full potential if contextual stimulation is not adequately presented. This is evident in the training programmes directly and exclusively targeting EF/SR stimulation, which lack durable and transferable effects. Therefore, recent research has shifted the attention towards malleable environmental factors; more specifically, to the role of school and classroom environment as an important developmental context for promoting children’s EF/SR skills and, in turn, their cognition and behaviour. Numerous observational studies have shown a correlation between the quality of teacher-student relationship (TSR) at the dyadic level or teacher-student interaction (TSI) at the classroom level and children’s EF/SR skills. To explore the direction of this association, the objective of this systematic literature review was to examine the causal effect of experiments and interventions that aim to improve children’s EF/SR by manipulating the TSI. Overall, the results from 18 included studies indicated that children in treatment groups show higher gains, albeit small-sized, in EF/SR performance compared to controls. Furthermore, TSI manipulation seemed to affect children’s SR skills more strongly than children’s EF skills. More importantly, the findings revealed the largest effects of these manipulations in children considered vulnerable or disadvantaged, suggesting that the cognitive deficits can be minimised if these children are supported appropriately. Given high study heterogeneity, this review highlights the need for more research (and interventions) explicitly investigating TSI and TSR and their potential impact on EF and SR in children. This study aims to provide information as to which specific aspects need to be examined more closely, instructing further development and implementation of efficient and effective interventions in education.